ZERO SOUND-VELOCITY IN PI, RHO-MESON GASES - Dey, J.; Dey, M.; Dearaujo, C. F.; Tomio, L. (World Scientific Publ Co Pte Ltd, 1994)
Sharp transitions are perhaps absent in QCD, so that one looks for physical quantities which may reflect the phase change. One such quantity is the sound velocity which was shown in lattice theory to become zero at the transition point for pure glue. We show that even in a simple bag model the sound velocity goes to zero at temperature T = T(v) not-equal 0 and that the numerical value of this T(v) depends on the nature of the meson. The average thermal energy of mesons goes linearly with T near T(v), with much smaller slope for the pion. The T(v) - s can be connected with the Boltzmann temperatures obtained from transverse momentum spectrum of these mesons in heavy-ion collision at mid-rapidity. It would be interesting to check the presence of different T(v) - s in present day finite T lattice theory.